Ferroptosis as an emerging target in sickle cell disease - Vitor Fortuna; Jaqueline Lima; Gabriel F. Oliveira; Yasmin S. Oliveira; Bruk Getachew; Sergei Nekhai; Michael Aschner; Yousef Tizabi (Current Research in Toxicology)
Sickle cell disease (SCD) is an inherited hemoglobin disorder marked by red blood cell sickling, resulting in severe anemia, painful episodes, extensive organ damage, and shortened life expectancy. In SCD, increased iron levels can trigger ferroptosis, a specific type of cell death characterized by reactive oxygen species (ROS) and lipid peroxide accumulation, leading to damage and organ impairments. The intricate interplay between iron, ferroptosis, inflammation, and oxidative stress in SCD underscores the necessity of thoroughly understanding these processes for the development of innovative therapeutic strategies. This review highlights the importance of balancing the complex interactions among various factors and exploitation of the knowledge in developing novel therapeutics for this devastating disease.